Temporal dynamic of adrenocortical and gonadal photo-responsiveness in male Japanese quail exposed to short days - Dominchin, Maria Florencia (2014)
The study evaluated whether different short-term endocrine testicular and adrenocortical responses to short photoperiod exposure can persist over time and particularly when birds exhibit spontaneous cloacal gland recovery. At 11 wk of age, 33 male Japanese quail exposed to long photoperiod were switched to short photoperiod (8L:16D). Another group of males was kept under long photoperiod (n = 11; LD quail). After 5 wk of short photoperiod exposure, quail were classified as nonresponsive or responsive to short photoperiod, depending on whether the cloacal gland volume was above or below 1,000 mm3 and with or without foam production, respectively. Since 11 wk of age and during a 20-wk period, droppings of all quail were collected to determine corticosterone and androgen metabolites (AM) by enzyme immunoassays. Cloacal gland volume was also determined weekly. Both short photoperiod nonresponsive (SD-NR) and responsive quail showed overall significantly lower (P < 0.01) AM values (518.8 ± 11.9 and 248.6 ± 17.1 ng/g, respectively) than quail that remained under long photoperiod (814.3 ± 24.1 ng/g). However, nonresponsive quail showed a significantly smaller reduction in their AM levels than their responsive counterparts. During the first 6 wk of short photoperiod exposure, SD-NR quail showed similar corticosterone metabolites values than LD quail. Corticosterone metabolite profiles changed from 7 wk of short photoperiod exposure onward, with photoperiodic differences (P < 0.01) persisting up to the end of study (LD: 228.9 ± 22.4 > SD-NR: 133.1 ± 15.5 > short photoperiod responsive: 61.6 ± 17.9 ng/g, respectively). Testicular and adrenocortical glands showed different degrees of activity associated with cloacal gland photoresponsiveness to short photoperiod manipulation. Our findings suggest long-term effects of short photoperiod, both in the hypothalamic-pituitary-gonadal and hypothalamic-pituitary-adrenocortical axis activity of quail, including males that exhibited spontaneous cloacal gland recovery.